Guía de aplicaciones clínicas In Vivo del Microscopio Confocal VivaScope® 1500 y 3000 - Acón Ramírez, Elizabeth (2019)
UCR::Investigación::Sistema de Estudios de Posgrado::Salud::Especialidad en Dermatología